Quality improvement in pediatric care - Moon Sung Park (Korean Pediatric Society, 2018)
We often overlook the importance of several safety issues such as identification of patients, timeout procedure, hand hygiene, handoff communication, and many others. This ignorance, along with many other issues, leads to medical error being ranked as a third leading cause of death in the U.S. Consequently, quality improvement (QI) has become one of the major subjects in healthcare despite a relatively short history. Improving quality is about making healthcare safe, effective, patient-centered, timely, efficient, and equitable. Understanding the need and methodology of QI as well as participation is now essential for physicians. Although basic QI methodology has not changed, one of the most fascinating changes in recent QI is conducting large-scale QI projects through multicenter networks. Prospective multicenter QI projects utilizing the Korean Neonatal Network are a substantial initiation of pediatric QI in Korea. The Korean Pediatric Society should set ambitious goals for QI activities for every primary care pediatrician and pediatric subspecialist.